Anti-diabetic activity of Allium wallichii on streptozotocin-nicotinamide-induced type-2 diabetes in rat (Bangladesh Journal of Pharmacology, 2022)
The aim of the present study was to investigate the effect of Allium wallichii leaves extract against streptozotocin-nicotinamide-induced type-2 diabetes in rats. The hydroalcohol extract of A. wallichii leaves (200 and 400 mg/kg) was tested for oral glucose tolerance test and in non-insulin-dependent diabetes mellitus-induced elevated serum glucose levels in the rat. Interestingly, single oral administration of A. wallichii caused a significant (p